The invisibility of indigenous names in the place names of the Jesuit missions of the Pampas (Buenos Aires, present-day Argentina) (Quinto Sol, 2024)
The Company of Jesus founded missions south of the city of Buenos Aires, present-day Argentina, between 1740 and 1753. The first in the vicinity of the Salado river, "Nuestra Señora de la Concepción de los Pampas", and two others in the Sierra del Volcán, "Nuestra Señora del Pilar del Volcán” and “Nuestra Señora de los Desamparados”. In this study we address the symbolic marks that allow us to trace their existence from their creation to the present. Specifically, we look into the transformation of place names that appear in written and cartographic records throughout the 18th and 19th centuries, complemented with observations made by scholars who traveled the region in the 20th century. In this way, we examine the transformations of the territory where the missions functioned with the aim of analyzing the process by which the Jesuits, called "padres", became part of the categories used to refer to the places inhabited by native peoples, today known as Laguna de los Padres and Sierra de los Padres.
Keywords: territory; religious mission; frontier; interethnic relations